Prestressed Voided Slab of Bridge Analysis Using CSI Bridge Analysis Tool - Sabir Khan; Dr. Tarun Kumar Rajak (International Journal of Scientific Research in Civil Engineering, 2025)
Bridge construction plays a vital role in the development of cities and, thus, has achieved great significance these days. It facilitates a free and undisturbed movement for traffic. It also plays an important role in the development of trade and industries, enhancing the progress of the nation. A prestressed concrete slab constitutes a great portion of bridges all around the world. Prestressed concrete was introduced into bridge construction in a very early period. In past decades, wide varieties of new techniques have been developed. Along with new developments in technologies, spans became longer, and the aesthetics and appearance of the bridge became more important. Prestressed concrete bridges include a wide variety of different forms like cast-in-situ or precast concrete, continuous or cable-stayed, simply supported; box-girders, slabs or beams. Among the wide variety of prestressed concrete bridges, a study on solid and voided slabs has been carried out. A comparison regarding forces and moment is done, thus, analyzing both cases for a better section to be used.